The Use of Migrant Labour - Threat or Advantage for Russian Economical Development? - Koretskaya-Garmash, Viktoria Aleksandrovna (Economy of Regions, 2016)
The article is devoted to a relevant problem of labour migration, the potentially possible threats and advantages of attracting and using of foreign migrant labour in the framework of the Russian economy are considered. The purpose of this work is to establish the how the migration processes influence over the current state of the Russian economy, and whether it is possible to meet the demand in the labour force by attracting labour migrants. The research method is the analysis of the statistical indicators of the Russian regions’ development, of demographic, migratory and financial situations in the Russian Federation. The results of the study are presented in the form of a quantitative assessment of the potential threats to the internal market due to the use of external migrant labour, which has already led to the Russian economic disruption, the devaluation of the Russian ruble, the growth of current account deficit, the load on the pension system of Russia. Therefore, we must not forget the positive aspects - rejuvenation of the age composition of the population, occupation of vacant jobs by the workers in the disadvantaged Russian regions, the increasing size of tax revenues to the Russian budget system by filing patents on employment activity. The presented results of the study can be used by public authorities in the migration policy, labour and social work for the development of the state programme stimulating internal and external migrants for employment in the regions with a shortage of manpower. The conducted research allows to define the relationship between labour migrants and economic activity of local population, to characterize the reasons of external labour migration and to analyse the consequences of migration for the host country.